The oldest Vespinae from the Paleocene of Menat (France) (Hymenoptera: Vespidae) - Nel, André; Auvray, Francis (Zootaxa, 2006)
Paleovespa menatensis sp. nov. is the oldest Vespinae to be described from the Paleocene of Menat (France). This subfamily could have diversified relatively recently, during the Late Paleogene, which could be congruent with its apparent absence in the Mesozoic.